Spatial facilitation and competition regulate tree species assembly in a tropical dry forest - Salazar Villegas, Mike H.; Wiegand, Thorsten; González-M, Roy; Rodriguez-Buritica, Susana; Qasim, Mohammed; Csaplovics, Elmar (Frontiers in Forests and Global Change, 2023)
Analyzing the spatial association pattern among species can help to better understanding the mechanisms that drive forest dynamics and assembly. We applied techniques of spatial point pattern analysis to data from a fully mapped plot of tropical dry forest (TDF) in Colombia to assess the spatial association network among the eight most abundant species and we tested the hypothesis that species traits related to the ability to cope with drought stress could explain the observed spatial association patterns. We conducted three analyses, first we classified the types of spatial association patterns of species pairs against a null model of spatial independence, second, we used a heterogeneous Poisson (HP) null-model to assess competitive and facilitative interactions, and finally, we integrated the spatial association network with a traits space spanned by hydraulic functional traits. Overall, the proportion of significant negative and positive associations were low and we found at smaller spatial scales (5m) prevalence of positive association patterns (11%) and at intermediate scales (16m) negative interactions (13%). The dominant, evergreen and bird-dispersed species T. oligofoliata, which followed a hydraulically save strategy, was involved in most positive associations at small scales, whereas the evergreen large statured species A. polyneuron, which also follows a conservative resource-use strategy, was involved in most negative interactions. In TDFs where water stress is prevalent, tree community assembly and spatial patterns formation are regulated by environmental heterogeneity (e.g. topography), and both facilitative and competitive processes act simultaneously, but at different spatial scales and involving different species. Our findings highlight the potential importance of the examined association patterns, not only for our understanding of community assembly, but also to provide restoration directions.